2015
DOI: 10.1016/j.ophtha.2015.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Study of Optimal Perimetric Testing In Children (OPTIC)

Abstract: Visual field size and sensitivity increase with age in patterns that are specific to the perimetric approach used. These developmental changes should be accounted for when interpreting perimetric test results in children, particularly when monitoring change over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 15 publications
0
48
0
Order By: Relevance
“…Children exhibited a level of interobserver variability similar to adults (SD ¼ 1.5 dB vs. 1.4 dB in adults), and the 1.9-dB deficit is consistent with previous data from ordinary static threshold perimetry. For example, Patel and colleagues 34 reported a 1.85-dB deficit among 9-to 11-year-olds (grid ¼ 6248), while Tschopp and colleagues 35 reported a~1-dB deficit in 7-and 8-year-olds (grid ¼ 638).…”
Section: Sensitivitymentioning
confidence: 99%
“…Children exhibited a level of interobserver variability similar to adults (SD ¼ 1.5 dB vs. 1.4 dB in adults), and the 1.9-dB deficit is consistent with previous data from ordinary static threshold perimetry. For example, Patel and colleagues 34 reported a 1.85-dB deficit among 9-to 11-year-olds (grid ¼ 6248), while Tschopp and colleagues 35 reported a~1-dB deficit in 7-and 8-year-olds (grid ¼ 638).…”
Section: Sensitivitymentioning
confidence: 99%
“…46,54 Contrary to previously reported studies, 44,45 a reduction in sensitivity with age was not observed. Adult-like sensitivity values, 46,54 range 19 to 38 dB, were observed in 7- and 8-year-old subjects.…”
Section: Discussionmentioning
confidence: 80%
“…However, our test completion success rate was similar to previous studies involving conventional strategies and a pediatric population. 44,45 During our clinical evaluation work, a smaller number of presentations were performed for a comparable test time to that presented in the literature. 4649 The long test duration to stimuli presentation ratio is a consequence of the game strategy used, and resulted from a longer than average interstimuli interval.…”
Section: Discussionmentioning
confidence: 99%
“…Non-seeing isopters were assigned negative area values in this study. It should be noted that in some previous publications, isopter groups have been referred to as isopters; 14,20,23,27,3032,37 the two terms should not be confused.…”
Section: Methodsmentioning
confidence: 99%
“…Popular methods include the use of software that can analyze scanned images of GVFs (e.g. Adobe Photoshop, 23,34,37 Engauge Digitizer, 32 GIMP, 27 JHU’s FieldDigitize, 7,10,24 MathWorks MATLAB, 14 NIH’s ImageJ, 18,31 Scion Image, 34,36 UCL’s Retinal Area Analysis Tool, 28 UTHSCSA ImageTool 29,33 ), or handheld devices to convey position information to computer software. 5,20,21,23,26 To our knowledge, however, none of these previous studies have explored the variability of calculated retinal areas or the error rates of digitizers.…”
mentioning
confidence: 99%